Study on the Characteristics of Small-Molecule Kinase Inhibitors-Related Drug-Induced Liver Injury - Dong, Huiqun; You, Jia; Zhao, Yu; Zheng, Danhua; Zhong, Yi; Li, Gaozheng; Weng, Zuquan; Luo, Heng; Jiang, Shan (Frontiers in Pharmacology, 2022)
Background: More than half of small-molecule kinase inhibitors (KIs) induced liver injury clinically. Meanwhile, studies have shown a close relationship between mitochondrial damage and drug-induced liver injury (DILI). We aimed to study KIs and the binding between drugs and mitochondrial proteins to find factors related to DILI occurrence. Methods: 1,223 oral FDA-approved drugs were collected and analyzed, including 44 KIs. Fisher exact test was used to analyze DILI potential and risk of different factors. 187 human mitochondrial proteins were further collected and high-throughput molecular docking was performed between them and drugs in the data set. The molecular dynamics simulation was usded to optimized and evaluated the dynamic binding behavior of the selected mitochondrial proteins/KIs complexes. Results: The possibility of KIs to produce DILI is much higher than other types (OR = 46.89, P = 9.28E-13). A few DILI risk factors were identified, including molecular weight (MW) between 400 and 600, the defined daily dose (DDD) ≥ 100mg/day, the octanol-water partition coefficient (LogP) ≥ 3, and the degree of liver metabolism (LM) more than 50%. Drugs that met this combination of rules were found to have higher DILI risk than controls (OR = 8.28, P = 4.82E-05) and were more likely to cause severe DILI (OR = 8.26, P = 5.06E-04). The docking results showed that KIs had significant higher affinity with human mitochondrial proteins (P = 4.19E-11) compared with other drug types. Furthermore, the five proteins with the lowest docking score were selected for molecular dynamics simulation, and the smallest fluctuation of the backbone RMSD curve was found in the protein 5FS8/KIs complexes, which indicated the best stablility of the protein 5FS8 bound to KIs. Conclusions: KIs were found to have the highest odds ratio of causing DILI. MW were significantly related to the production of DILI. And the average docking scores of KIs drugs were found to be significant different from other classes. Further analysis identified the top binding mitochondrial proteins for KIs and specific binding sites were analyzed. The optimization of molecular docking results by molecular dynamics simulation may contribute to further study the mechanism of DILI.